ENHANCING THE TEACHING OF SCIENCE THROUGH THE USE OF ICT IN SENIOR SECONDARY SCHOOLS (UNIZIK Journal of STM Education, 2021)
Information and Communication Technology (ICT) is an important area that cannot be ignored in education because of the demand due to technological growth in both the private and public sectors of the country’s economy. Science teachers need to bring their ICT knowledge up to date since ICT tools are considered to be an efficient way to extend the horizons of traditional science teaching. ICT tools can also support learning strategies where students’ projects are involved thereby improving and enhancing students’ interest. This paper examined the concept of ICT; application of ICT in science education; the benefit of ICT in science teaching and learning; challenges to the use ICT in teaching and learning of science. Some solutions to these problems were also suggested.
Keywords: Information and communication technology; teaching; science education